Existential Crisis through Conflicts in Iñárritu’s "Birdman" or (The Unexpected Virtue of Ignorance) - Yudia, Yudia; Sutandio, Anton (Indonesian Journal of Visual Culture, Design, and Cinema, 2022)
This paper aims to explore the existential crisis through conflicts in Alejandro González Iñárritu's film, Birdman or (The Unexpected Virtue of Ignorance) (2014). The film won numerous awards including the prestigious Academy Awards in 2015. Iñárritu is dubbed as the most successful Mexican director with his other notable films such as Amores Perros (2000), 21 Grams (2003), Babel (2006), and The Revenant (2015). This paper borrows Sartre's existentialist theory to reveal the conflicts that the protagonist, Riggan Thomson, experiences. The discussion on the film cinematography is also done to show how the film visually depicts and emphasizes the existential crisis through the conflicts. The findings reveal that the main cause of Thomson's conflicts is his ambition to have a meaningful life and define his existence. All his conflicts, both internal and social, show that Thomson first exists as a "Birdman" that does not reflect who he is as a human being. Thus, the conflicts become a part of his journey to find his essence and to free himself from the shadow of the Birdman.